Black Sexualities : Probing Powers, Passions, Practices, and Policies - Barnes, Sandra L.; Battle, Juan, 1968- (Book collections on Project MUSE., 2010)
Contains twenty articles in which various authors explore issues in the field of Black sexualities, covering identity theories and frameworks; descriptions, depictions, and responses; citizenship, activism, and legal dynamics; systemic and personal stresses; and the life course.